MAHALLA, THE PILLAR OF NEW UZBEKISTAN - Rakhimov Ilkhomjon; Tishabayeva Lola (Bright Mind Publishing, 2025)
The article aims to eliminate the problems in assessing the importance of the reforms and positive changes in the effective organization of the work of self-government bodies “Mahalla Yettiligi” taking place in Uzbekistan in recent years, their rapid penetration into all spheres of life, and the significance of the system in the structure of self-government. Research methods used in conducting the research were comparative and critical study and analysis of political and sociological literature on the problem. Research results Suggestions were made to the mahalla chairmen in this regard in order to effectively organize and evaluate the work of “Neighborhood Seven” in our country.
Keywords: “Neighborhood Seven”, Digitalization, indicator, performance indicators (KPI), Mahalla, globalization, Evaluation, electronic platform, citizens